The Effect of Inter-Sectoral Links on the Dynamics of Human Capital in Polish NUTS II Level Regions - Andrzej Cieślik; Tomasz Misiak (Studia Regionalne i Lokalne)
The main goal of this article is to investigate how the structure of inter-sectoral links affects the dynamics of human capital. This structure has been split into related variety (RV) and unrelated variety (UV). The assembled empirical evidence shows that RV positively affects the rate of human capital growth in a region, while UV has negative effects both in the group of all Polish regions and in the most developed regions located in western Poland. Moreover, among all the analysed control variables, only RV determines the existence of the effect of human capital convergence.